Type 2 Diabetes Affects Joint Pain Severity in People with Localized Osteoarthritis: A Retrospective Study - Alenazi, Aqeel M (Pain Med, 2020)
OBJECTIVE: To examine the association between type 2 diabetes (T2D) and pain severity in people with localized osteoarthritis (OA) and to explore the association between glycemic control, measured by hemoglobin A1c (HbA1c) level, and pain severity in people with localized OA and T2D. DESIGN: Retrospective study. SETTING: A tertiary medical center. SUBJECTS: Data from 819 patients (mean age = 65.08±9.77 years, 54.3% women) were used. METHODS: Patients were grouped to localized OA only (N = 671) and localized OA+T2D (N = 148) based on diagnosis codes. An index date was set as the first diagnosis date of localized OA and linked to pain severity, measured by numeric rating scale from 0 to 10. HbA1c values were obtained for patients with T2D within six months of the index date. Multiple linear regression was used. RESULTS: After controlling for age, gender, body mass index (BMI); diagnoses of depression, hypertension, dyslipidemia; OA locations; and medication list (+/- 90 days of the index date), T2D was significantly associated with increased pain severity (B = 1.07, 95% confidence interval [CI] = 0.25 to 1.88, P = 0.014). For patients with T2D and localized OA with available data for HbA1c (N = 87), the results showed that an increased HbA1c value was significantly associated with higher pain severity (B = 0.36, 95% CI = 0.036 to 0.67, P = 0.029) after controlling for age, gender, BMI, medications, and OA locations. CONCLUSION: T2D was associated with higher pain severity in people with localized OA, and poor glycemic control was associated with higher pain severity in people with localized OA+T2D. Clinicians should emphasize that better HbA1c control might help with pain management in people with T2D and OA.